Processing: free choice at no cost - Chemla, Emmanuel; Bott, Lewis (Proceedings of the Amsterdam Colloquium, 2011)
A disjunctive sentence such as (1) standardly carries the conjunctive inference that (2)a and (2)b are true. (1) (2) John is allowed to eat an apple or a banana. a. John is allowed to eat an apple. b. John is allowed to eat a banana. This phenomenon is known as Free Choice (FC) permission (Kamp, 1973). Current formal models tend to treat FC inferences as a special type of scalar implicature (mostly building on Kratzer and Shimoyama’s 2002 insight, see, e.g., Schulz, 2003; Fox, 2006; Klinedinst, 2006; Alonso-Ovalle, 2008; Chemla, 2008, 2009; Franke, 2011). We present the first processing study of FC. Our results go against the expectations of recent formal analyses, and show that, unlike scalar implicatures, FC inferences come at no processing cost.